THE ROLE PLAYED BY THE STAKEHOLDERS IN THE INDUSTRIALIZATION OF THE ART OF CRAFT AT TEGALLALANG, GIANYAR, BALI - Sila, I Nyoman; Ardika, I Wayan; Atmadja, Nengah Bawa; Dhana, I Nyoman (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2017)
The industrialization of the art of craft at Tegallalang, Gianyar, Bali results from the technological, economic and cultural development and leads to the production of different types of products of the art of craft. The industrialization of the art of craft cannot be separated from the role played by the stakeholders in order to obtain benefit. The problems of the study are as follows (a) what stakeholders play roles in the industrialization of the art of craft at Tegallalang, Gianyar, Bali? (2) How the stakeholders play their roles in the industrialization of the art of craft at Tegallalang, Gianyar, Bali? This present study is a qualitative one in which the critical theory of social practice proposed by Bourdieu and the ethnographic approach are used. The result of the study shows that the stakeholders playing roles in the industrialization of the art of craft at Tegallalang, Gianyar, Bali include the parents, the traditional village, the administrative village, the local government, the provincial government, craftsmen, the raw material supplier, the formal and informal financial institution, and foreign consumers. The stakeholders play their roles using different capitals such as the cultural capital, social capital, and economical capital. Those who have big capitals will dominate those who have fewer capitals and organize what products should be produced.